Making With Place: Community Artists Theorizing Change (LEARNing Landscapes, 2024)
This article confronts tensions of “risk” and “change” in youth engagement and community arts, towards insights for alternate world-building. We problematize overly instrumental approaches, by examining aesthetic and inductive theories of change arising from Making With Place, a research creation initiative based in Toronto, Canada. From Spring 2020 to Fall 2022, we engaged diverse young people as artist-researchers in community arts production experiments exploring concepts of place from individual and collective perspectives. We draw here on resulting public artworks, discussions with the artists, and our own field notes to surface the theories of change arising from this work. We identify three emergent metaphors—the garden, the bridge, the margins—and the ways in which they resist dominant discourses in favor of new practices of imagination and repair. We explore how these creative explorations articulate theories of change that refuse forgetting and call forth desire.
Keywords: youth artists-researchers; community arts; co-theorizing; theories of change